Uma proposta de ensino-aprendizagem para o desenvolvimento de projetos em equipes ágeis de estudantes da Graduação - Silva, Ulisses Gonçalves da (2024)
In Undergraduate Education, the development of team projects is a strategy employed by teachers to foster students' learning of specific content, problem-solving skills, and practical skill development within their respective fields of knowledge. However, in undertaking such projects, students encounter a range of difficulties, including: lack of skills to comprehend project demands, absence of strategies for organizing teamwork, and challenges in building cooperative relationships to achieve proposed objectives. Given this issue, this research aimed to design a teaching-learning proposal that organizes the development of team projects for undergraduate students, anchored in Project-Based Learning and SCRUM methodologies to develop both hard and soft skills. This qualitative research adopted action research as its methodological path and resulted in the development of an educational product called LEVE - an approach for agile team project development among students, materialized in the form of a website that systematizes the teaching-learning proposal, enabling its application by other teachers. The evaluation of LEVE was conducted with students in the 4th semester of the Technology in Systems Analysis and Development (TSAD) program at the Instituto Federal do Amazonas - IFAM (Federal Institute of Amazonas). As a result of the product application, regarding hard skills, it was observed that teams with better understanding of the problem also achieved better results in delivering their artifacts. Concerning soft skills, teamwork required information sharing, providing a context for developing communication skills, and specifying a moment for task planning and monitoring allowed the development of management skills.